2016
DOI: 10.1063/1.4948484
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pedestal gradient characteristic on the Experimental Advanced Superconducting Tokamak

Abstract: A pedestal database was built based on type I edge localized mode H-modes in the Experimental Advanced Superconducting Tokamak. The most common functional form hyperbolic tangent function (tanh) method is used to analyze pedestal characteristics. The pedestal gradient scales linearly with its pedestal top and the normalized pedestal pressure gradient α shows a strong correlation with electron collisionality. The connection among pedestal top value, gradient, and width is established with the normalized pedesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is usually found in experiment that pedestal stored energy is proportional to total energy [39], which is attributed to core profile stiffness. The experimental results have shown that core density and temperature profiles are actually stiff on EAST [40]. Therefore, it is reasonable to assume ΔW ped,inter-ELM ∝ ΔW MHD,inter-ELM , where ΔW MHD,inter-ELM represents the increment of W MHD between two ELMs.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…It is usually found in experiment that pedestal stored energy is proportional to total energy [39], which is attributed to core profile stiffness. The experimental results have shown that core density and temperature profiles are actually stiff on EAST [40]. Therefore, it is reasonable to assume ΔW ped,inter-ELM ∝ ΔW MHD,inter-ELM , where ΔW MHD,inter-ELM represents the increment of W MHD between two ELMs.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…i On the other hand, large n e usually corresponds higher density pedestal [17], which can provide more bootstrap current, leading to lower l .…”
Section: Lhcdmentioning
confidence: 99%